Laboratory experiments and modelling of the geochemical interaction of a gabbro-anorthosite with seawater and supercritical CO2: A mineral carbonation study - Berrezueta, Edgar (2023)
The potential for mineral carbonation of carbon dioxide (CO2) in a plutonic mafic rock is addressed in this work through a set of laboratory experiments on a gabbro-anorthosite sample from the Torrão - Odivelas Massif (Portugal). The experiment was conducted in two stages under pressure (8 MPa) and temperature (313.15 K) conditions similar to those expected around a CO2 injection well. Stage-I simulated dissolution conditions, with a crushed rock sample (1–3 mm) exposed for 30 days to CO2 supersaturated seawater (0.576 M). Stage-II favoured carbonation conditions; cubic rock specimens (8 cm3) were brought in contact with the Stage-I seawater subsaturated in CO2 (0.095 M). A multi-analytical methodology was applied to follow the mineralogical and geochemical evolution of rock and seawater during both stages. At the end of Stage-I, the aqueous phase showed a marked increase in iron (Fe), magnesium (Mg) and calcium (Ca) ions and milder increase in silicon (Si) and aluminium (Al) ions. At the end of Stage-II, a decrease in Si and Al concentrations was observed while the Fe, Mg, Ca concentrations still increased, albeit at a lower rate. No significant geochemical variations were detected in the bulk solid phase. The bulk X-ray diffraction (XRD) analyses detected halite as a new mineral phase, while the grazing-XRD design revealed the presence of dolomite. Moreover, the elemental distribution mapping demonstrated the spatial association of carbon with magnesium indicating magnesite crystallisation. The geochemical model developed in CrunchFlow code was able to reproduce the experimental observations and simulate the chemical behaviour for longer time periods. Overall, the experiments and model point towards a mineral carbonation potential in the Torrão - Odivelas Massif, with further studies being required to upscale the laboratory results to field scale.